Development of Manga comic learning media “Immunity at Work” for high school students - Farhan Ramadhan; Ainul Uyuni Taufiq; Andi Tenri Ola Rivai; Jamilah Jamilah (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
The development of the educational era that is growing very quickly certainly requires the provision of relevant learning resources, especially the availability of additional teaching media that can have a positive influence on the motivation and learning outcomes of students. The goal of this research is to create a Manga “Immunity at Work” learning media that fits the criteria of validity, practicality, and effectiveness. Using the ADDIE approach, this study conducts R&D (Research and Development) research. The development product was evaluated using validity, practicality, and effectiveness tests. The research subjects were validators (validation experts), biology educators (practitioners), and students from grade XI MIA II at MA Madani Alauddin Pao-pao. The research instruments were in the form of media validation sheets, educators and students’ response questionnaires, and learning outcomes test items. The results showed that the developed media had a validity level of 3.56 (very valid), the level of practicality based on the response assessment of educators was 97.5% (very practical) and students 85.31 (very practical). The learning outcomes test has a percentage of classical effectiveness level of 85% reaching the minimum value for the effective category. Based on the findings of this research, the development of the Manga learning media “Immunity at Work” is recommended to be optimized in dissemination, similar development, and application.Abstrak. Perkembangan era pendidikan yang berkembang dengan sangat cepat tentunya memerlukan penyediaan sumber belajar yang relevan, terutama ketersediaan media ajar yang tambahan yang mampu memberikan pengaruh positif terhadap motivasi dan hasil belajar peserta didik. Penelitian ini bertujuan untuk mengembangkan media pembelajaran Komik Manga “Immunity at Work” yang memenuhi kriteria kevalidan, kepraktisan dan keefektifan. Penelitian ini menggunakan jenis penelitian R&D (Research and Development) dengan model ADDIE. Produk pengembangan diuji melalui uji validitas, uji kepraktisan dan uji keefektifan. Subjek penelitian adalah validator (ahli validasi), pendidik mata pelajaran Biologi (praktisi), dan peserta didik kelas XI MIA II di MA Madani Alauddin Pao-pao. Instrumen penelitian berupa lembar validasi media, angket respon pendidik dan peserta didik, serta butir-butir tes hasil belajar. Hasil penelitian menunjukkan bahwa media yang dikembangkan memiliki tingkat validitas yaitu 3.56 (sangat valid), tingkat kepraktisan berdasarkan penilaian respon pendidik yaitu 97.5% (sangat praktis) dan peserta didik 85.31 (sangat praktis). Tes hasil belajar memiliki persentase tingkat keefektifan secara klasikal 85% mencapai nilai minimum untuk kategori efektif. Berdasarkan temuan dari penelitian ini, pengembangan media pembelajaran Komik Manga “Immunity at Work” direkomendasikan untuk dioptimalkan dalam penyebarluasan, pengembangan serupa, maupun penerapannya.